Numerical investigation of pollutant transport characteristics inside deep urban street canyons - Li, Xian-Xiang; Liu, Chun-Ho; Leung, Dennis Y.C. (Atmospheric environment (1994), 2009)
A validated LES model was employed to simulate the street canyons of aspect ratio (AR) 3, 5, and 10. Three, five, and eight vertically aligned primary recirculations were found for the three cases, respectively, which showed decreasing strength with decreasing height. The ground-level wind speeds were found to be very small, making it extremely difficult for the ground-level pollutants to disperse. Local maxima of turbulence intensities were found at the interfaces between the primary recirculations and the shear layer. The pollutant trajectory followed the primary recirculations. High pollutant concentration and variance were found near the buildings where wind flowed upward. Large gradients of pollutant concentration and variance were also observed at the interfaces between the primary recirculations and the shear layer. Detailed analyses of concentration budget showed that the advection terms were responsible for pollutant redistribution within primary recirculations, while the turbulent transport terms were responsible for pollutant penetration between primary recirculations as well as pollutant removal from the street canyon.